Vpliv evropskega prava na ureditev zunajsodnega reševanja sporov - Damjan, Matija (Pravni letopis, 2008)
The use of various forms of alternative dispute resolution outside classical judicial procedures is growing in Europe. These include especially the mediation and conciliation and, in a wider sense, also the arbitration. These procedures can facilitate access to justice for individuals and are appropriate for easier resolution of cross-border disputes in the single European market. For this reason, the EU demands that Member States encourage the use of such procedures, and promotes the self-regulation of the bodies, dealing with out-of-court dispute resolution. Directive 2008/52/EC is the first legally binding EU document that determines some of the elements of legislative regulation of the mediation itself. Thus far, EU acts intended to increase the quality of mediation were legally not binding and were mostly in the form of recommendations. Apart from the EU, other international organisations are dealing with out-of-court dispute resolution as well, such as the Council of Europe, OECD and UNCITRAL. The new Slovenian legislation on mediation has been formed under intensive influence of these international legal sources.
Keywords: alternativne oblike; European Union; Evropska unija; nepravdni postopek; reševanje; Slovenia; Slovenija; spori